The kinematics of the return of serve in tennis: The role of anticipatory information - Carboch, J.; Button, C.; Süss, V. (The Sport Journal, 2012)
Visual anticipatory information from early periods of ball flight is thought necessary to intercept the ball in many sports. This study analyzed the temporal characteristics of returning a tennis serve by manipulating the amount of visual information available to the receiver. The movements of tennis players receiving `serves` were measured on court. Participants received serves when playing against a ball machine or an actual server during full vision conditions and also during partial vision occlusion (i.e., early ball flight, second third, last third of ball projection). We measured the moment of the receiver`s movement initiation; the back swing duration; and the forward swing duration. There were no consistent differences in these movement characteristics between the ball machine and the server up to the projection speed of 125 km/h. There were differences in the duration of the forward swing during the partial vision conditions. Initiation of the forward swing occurred earlier and the swing duration was increased when the first third of ball flight was occluded. Important anticipatory information about when to initiate the forward swing is present during the first third of ball flight. When receiving moderately fast serves up to 125 km/h, the receiver does not appear to use information from the server`s action to modify the timing of their response.